Investigation of bacterial gut microbiome in diverse Egyptian populations “pilot study”: Gut microbiome among Egyptians - Mohamed, Kareem Talaat; Shabayek, Sarah; Fahmy Mahmoud, Nora; Tawfick, Mahmoud Mohamed; Hanora, Amro Mohamed Said (Cellular and Molecular Biology, 2025)
The gut microbiota plays a huge role in human health regarding immunity, metabolism, and nutrient absorption. In this work, the gut microbiota, with its bacterial community structure, is studied using whole genome shotgun (WGS) sequencing for populations from two different geographical regions in Egypt: Cairo (urban) and Ismailia (rural). Fecal samples were obtained from six healthy individuals, three from Cairo and three from Ismailia, of ages ranging from 43 to 52 years. Alpha diversity, measured as Shannon, inverse Simpson, and OTUs, showed no significant differences between the two cities. However, beta diversity analysis by Principal Coordinate Analysis (PCoA) revealed diverse microbial compositions. Thus, only the Ismailia samples contained higher levels of butyrate-producing bacteria involved in maintaining intestinal health, such as Faecalibacterium prausnitzii and Akkermansia muciniphila. On the other hand, there was a higher prevalence in Cairo of bacteria associated with protein and fat metabolism, like Bacteroides thetaiotaomicron. Such findings explain the influence of environmental factors in shaping gut microbiota and show that to get a comprehensive understanding of regional differences, many wider-ranging studies need to be conducted.